2019
DOI: 10.1534/g3.119.400336
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Genomic Multi-output Regressor Stacking Model for Predicting Multi-trait Multi-environment Plant Breeding Data

Abstract: In this paper we propose a Bayesian multi-output regressor stacking (BMORS) model that is a generalization of the multi-trait regressor stacking method. The proposed BMORS model consists of two stages: in the first stage, a univariate genomic best linear unbiased prediction (GBLUP including genotype × environment interaction GE) model is implemented for each of the L traits under study; then the predictions of all traits are included as covariates in the second stage, by implementing a Ridge regression model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…(2018) and Montesinos‐López et al. (2019c, 2019d), in which a small gain in terms of prediction performance is obtained with regard to univariate deep learning prediction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2018) and Montesinos‐López et al. (2019c, 2019d), in which a small gain in terms of prediction performance is obtained with regard to univariate deep learning prediction.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, the BMTME generalizes conventional multi-trait analysis (which takes into account the correlation between traits) to also take into account the correlation between environments. In the context of deep learning, there are applications of multi-trait deep learning for genomic selection such as those published by Montesinos-López et al (2018) and Montesinos-López et al (2019c, 2019d, in which a small gain in terms of prediction performance is obtained with regard to univariate deep learning prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stacking a large number of base learners requires a level-2 model to perform the multicollinearity data analysis in the model [78]. Thus, ridge regression, least absolute shrinkage, selection operator (LASSO), and elastic net regression (ENET) can be used as level-2 models for collinearity analysis [78][79][80][81]. The grain yield predictions made by single models under full and limited irrigation treatments were similar across the growth stages, indicating the adaptability of UAV data for grain yield prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic information is available in the form of the Genomic Relationship Matrix (obtained from centered and standardized marker data). Both phenotypic and genomic data were previously used in Montesinos-López et al (2019) and can be found in https://data.cimmyt.org/data set.xhtml? persistentId=hdl : 11529/10548141.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple trait selection is a concern addressed by animal and plant breeding in the past ( Smith 1936 ; Hazel 1943 ; Henderson and Quass 1976 ) and also in the era of GS ( Sun et al 2017 ; Montesinos-López et al 2019 ; Neyhart et al 2019 ; Lenz et al 2020 ). Multi-trait selection models are promising because they have the potential to increase the accuracy of GEBV (given that they use information about genetically correlated traits), especially in the presence of low heritability traits ( Jia and Jannink 2012 ; Guo et al 2014 ; Ward et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%